PENGARUH CURAH HUJAN PADA TEGANGAN AC LEWAT DENYAR ISOLATOR TONGGAK - , MUHAMMAD BINTANG ASSYIDIK ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Post insulator is an electrical power system equipment that is used for isolating one conductor from any other conductors. Post insulator have a failure situation when flashover occurs. The use of post insulator as an outdoor insulation need to know the value of ac voltage that can be held by an insulator during rain condition. This research was conducted to determine the value of ac post insulator flahsover voltage on line post insulator and pin post insulator during rain conditions. Testing was done by applying ac voltage to the post insulator until flashover occuring when it given artificial rain having rainfall rate of mm/minute up to 5,5 mm/minute. The result showed that line post insulator had flashover voltage of 110 kV during dry condition and 65 kV during wet condition, while pin post insulator had flashover voltage of 130 kV during dry condition and 70 kV during wet condition. This difference of value is due to the different construction for each insulator type. It was found from the research data that the value of flashover voltage decrease along with increase rainfall rate applied. Pin post insulator had higher value of flashover voltage than line post insulator, therefore it is better to use pin post insulator in areas with high rainfall rate.